Electrochemical behavior of lanthanum and yttrium ions in two molten chlorides with different oxoacidic properties: The eutectic LiCl-KCl and the equimolar mixture CaCl2-NaCl - Castrillejo Y.; Bermejo M.R.; Martínez A.M.; Díaz Arocas P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The electrochemical behavior of LaCl3 and YCl3 was studied in two molten chloride mixtures with different oxoacidic properties, the eutectic LiCl-KCl and the equimolar CaCl2-NaCl melt at different temperatures. The stable oxidation states of both elements have been found to be (III) and (0) in both melts, and it was found that both La(III) and Y(III) cations were less solvated by the chloride ions in the calcium-based melt, which was explained by the stability of CaCl4 2- ions in that melt. Transient electrochemical techniques, such as cyclic voltammetry, chronopotentiometry and chronoamperometry were used in order to study the reaction mechanism and the transport parameters of electro active species at a tungsten electrode. The results showed that in the eutectic LiCl-KCl, the electro crystallization of lanthanum and yttrium seems to be the controlling electrochemical step while in CaCl2-NaCl this phenomenon has not been observed. That was explained in terms of the differences in the physicochemical properties of the systems, especially interfacial tensions. In the eutectic LiCl-KCl chronoamperometric studies indicated instantaneous and three dimensional nucleation and crystal growth of lanthanum and yttrium whatever the applied over potential of the rare earth metal is, whereas in the equimolar mixture CaCl2-NaCl, the corresponding electrochemical exchanges were found to be quasi-reversible, and the values of the kinetic parameters, K0 and α,were obtained for both reactions. Mass transport towards the electrode is a simple diffusion process, and the diffusion coefficients have been calculated. The validity of the Arrhenius law was also verified by plotting the variation of the logarithm of the diffusion coefficient versus 1/T.